Practice-dependent modulation of neural activity during human sensorimotor coordination: a functional Magnetic Resonance Imaging study - Jantzen, K.J.; Steinberg, F.L.; Kelso, J.A.S. (Neuroscience letters, 2002)
We investigated the degree to which differences in the pattern of blood oxygen level dependent activity (BOLD) between syncopated and synchronized coordination patterns are altered by practice. Baseline levels of BOLD activity were obtained from eight subjects while they syncopated or synchronized with an auditory metronome at 1.25 Hz. Subjects then practiced syncopation at the same rate for four consecutive sessions. Post practice scans of the two coordination patterns were then performed. Before practice, baseline syncopation activated a much broader network of both cortical and subcortical regions than synchronization that included Supplementary Motor Area (SMA), bilateral putamen, left thalamus, bilateral superior temporal gyrus as well as the vermis. This pattern of activity is hypothesized to reflect the extra timing and attention requirements of syncopation. After practice, activity in superior temporal gyrus and vermis were no longer observed during syncopation reflecting a reduction in the need for attention and the use of sensory feedback for guiding behavior. Surprisingly, post practice synchronization resulted in additional significant activations in SMA, inferior frontal gyrus and superior temporal gyrus as well as small activations in bilateral putamen. Practice with the more difficult syncopation task thus had a dual effect of decreasing the number of active regions during syncopation and increasing the number of active regions during synchronization. Since overt syncopation performance did not change significantly as a result of practice, these observed neural changes appear to be due to context- and history-dependent factors, rather than behavioral learning per se.